Toxic effects of five plant extracts against the larger grain borer, Prostephanus truncatus - Mweshi Mukanga; Yakub Deedat; Felix S. Mwangala (African Journal of Environmental Economics and Management, 2019)
Dried leaf powders of Eucalyptus, Guava, Neem, Tephrosia and Water hyacinth were evaluated for their insecticidal activity against Prostephanus truncatus Horn. The powders were tested at 0.1, 0.25, 0.5, 0.1, 2.5 and 5 g/100 g of dried cassava chips or flour. Data was collected on larvae and adult mortality, larvae and adult emergence, antifeeding, and repellency. The effects varied with plant species and dose rate. Increased insect deformity and mortality and reduced fecundity were observed among the leaf powder treatments compared to untreated control. The percentage reduction in the adult insect numbers ranged from 37.2 to 99.2% and was highest in the Neem, Tephrosia and Water hyacinth treatments. Neem had the highest larvicidal effects though not significant different (P > 0.5) from the other four plant species. On the other hand, Tephrosia and Guava leaf powders exhibited both strong repellent and anti-feeding effects. The petroleum ether extracts of the leaf powders of Neem and Guava were highly toxic on P. truncatus. The results suggest that these materials tested have the potential in development of post-harvest protection technology against, P. truncatus, the major pest of stored grains and dried cassava.